BENEFITS OF READING BOOK AND READING CULTURE OF MODERN GENERATION - Turakulova Nilufar Mamarayim’s daughter, (Ustozlar uchun, 2025)
This article explores the profits of reading. Reading book is one of the most effective ways to develop thinking of human knowledge and increase creativity. Books have played main role in human progress. Moreover, they are essential part of education,  traditions,  cultures and individual development. Nowadays, structures and habits of reading have significantly changes because of internet and digital technologies.